Vpliv anksiolitika na kvaliteto življenja in na kardiovaskularno avtonomno funkcijo pri bolniku s posturalno ortostatsko tahikardijo - Kavčič, Niko (Medicinski razgledi, 2005)
Postural orthostatic tachycardia syndrome (POTS) is a disorder of the autonomic nervous system. The pathology is characterised by adrenergic and cardiovagal nerve fibre dysfunction, combined with central abnormality of autonomic regulation. When assuming the upright posture or performing the tilttable testing, patients develop excessive tachycardia and symptoms such asdizziness, syncope, palpitations, anxiety. These are often present even in the absence of any decrease in arterial pressure. Patients with POTS experience limitations in multiple domains of quality of life. A variety of approaches have been used to alleviate symptoms of POTS, including anxiolytic therapy. The aim of the present work was to investigate the efficacy of anxiolytic therapy in patients with POTS. The patients were selected from the neurocardiologic laboratory archives on the basis of orthostatic tachycardia and orthostatic intolerance development upon tilt testing. They completed a set of questionnaires that included measures of quality of life (SF-36) and autonomic symptom severity (ASP). In order to evaluate autonomic nervous system function, blood pressure and ECG during rest, deep breathing, Valsalva maneuver, cold face test and tilt table testing were monitored. After alprazolam therapy for a period of four to five weeks, eleven patients were surveyed and retested. The results show that anxiolytic therapy in patients with POTS does not improve quality of life, nor does it decrease symptoms of orthostatic intolerance or normalise autonomic abnormalities. The results alsoindicate that anxiety does not play a major role in the pathophysiology ofthis disease.
Keywords: Anksiolitiki; Tachycardia; Diagnosis; Drža; Drug Therapy; Nagnjena miza, testi; Posture; Tahikardija; ankete; Anti-Anxiety Agents; Tilt-Table Test; Elektrokardiografija; Electrocardiography; Srčna frekvenca; Valsalvin manever; Heart Rate; Valsalva'S Maneuver; avtonomno živčevje; motnje; Questionnaires; therapy; diagnostika; zdravljenje